Structure and activity of factor D̄ of the alternative pathway of human complement - Schneider, D; Johnson, Diana Margaret Ashley (1981)
﻿ 1. A method for the purification of the serine protease,factor D,was developed using conventional chromatographic procedures. The final product was homogeneous as judged by SDS/polyacrylamide gel electrophoresis, its migration as a single component in ion exchange and gel filtration media, and its amino acid sequence analysis. The molecule had an apparent molecular weiyht of 24,000. It contained <1.5% (w/w) reducing sugars as judged by periodic acid/Schiff staining, and existed as a monomer in buffers containing either EDTA or calcium ions. 2. Approximately 84% of the amino acid sequence was established unequivocally by automated sequence analysis of the intact molecule and peptides derived by digestion with CNBr, o-iodosobenzoic acid, trypsin and V8 protease. Carboxypeptidase-Y digestion was used to establish the C-terminal amino acid. The peptides were aligned either by homology with other serine proteases, or by the overlap of sequences obtained from peptides derived by different fragmentation procedures. The molecule nad a typical serine protease-type sequence with isoleucine as the Nterminal amino acid. The active site serine and aspartic acid and the surrounding sequences were conserved as well as the sequence around the position of the active site histidine, although this residue itself was not identified. 3. The possibility of the existence of a factor D̄ zymogen which can be activated by trypsin was reinvestigated, but no evidence for a precursor was found. No enzymic activity towards a number of p-nitroanilide substrates and arginyl and lysyl esters was observed with factor D̄,but it was found to release p-nitrophenol from p-nitrophenyl-p'-guanidinobenzoate. Factor D̄ was inhibited by diisopropylphosphofluoridate and p-nitrophenyl-p'-guanidinobenzoate, but a variety of other non-protein and protein inhibitors including α2-macroglobulin, c1 inhibitor and inter-α-trypsin inhibitor had no effect on enzymic activity.